2012
DOI: 10.1016/j.mineng.2012.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and Fe(III) ions on chalcopyrite bioleaching by an adapted consortium from biogas sweetening

Abstract: Particle size, pH and Fe(III) ions affect the process of bioleaching of copper from chalcopyrite ores. In the study presented herein a copper sulfide ore was subjected to bioleaching process using a mixed microbial consortium obtained from a biotrickling filter treating high loads of H 2 S at different mineral particle size, distinct medium pH and various additional Fe(III) ion concentrations as leaching agent. After 1300 hours of operation, the total copper recovery achieved a value of 50 % in the most acidic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 14 publications
0
21
0
1
Order By: Relevance
“…Several studies have been focused on the effects of H + , Fe 3+ , temperature and leaching bacteria on the bioleaching process [13,14]. The results implied that H + and Fe 3+ are of great benefit for the bio-oxidation and decomposition of sulfide minerals.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been focused on the effects of H + , Fe 3+ , temperature and leaching bacteria on the bioleaching process [13,14]. The results implied that H + and Fe 3+ are of great benefit for the bio-oxidation and decomposition of sulfide minerals.…”
Section: Introductionmentioning
confidence: 99%
“…The particle size used in the bioleaching experiments was between 2 and 3 mm, following the recommendations of Dorado et al 19 To obtain this size, the mineral was ground with a hammer mill (Serie 24, Humboldt Wedag Española SA, Spain) and sieved to the desired diameter range.…”
Section: Methodsmentioning
confidence: 99%
“…In this sense, it is well known that the use of pure cultures of Acidithiobacillus ferrooxidans or Acidithiobacillus thiooxidans in bioleaching results in high extraction yields of copper from minerals such as chalcopyrite 16 . However, mixed consortiums, containing these types of microorganisms can also be used for this purpose with several advantages such as the capacity to be adapted to the process in a short time and, thus, they are an economic alternative with greater potential for widespread use 17‐20 . In addition, it has been reported that the mixed consortia can be more efficient than pure culture since can be adapted easily to the process 21 …”
Section: Introductionmentioning
confidence: 99%
“…Recently, bioleaching has been proposed as an alternative to conventional physical-chemical processes, showing important advantages such as low cost, high efficiency and environmental friendliness [8]. Bioleaching process has been studied for many years in the mining field [9][10][11], especially when low-grade ores have to be treated, due to the low cost of bioleaching process [12]. This technique, which has proven to be effective in this field, has been extended for the metal extraction from other possible metals sources [13,14].…”
Section: Introductionmentioning
confidence: 99%